Association between thyroid function and prognosis of severe COVID-19 among patients with SARS-CoV-2 infection: a retrospective cohort study in China - Yang, Yaling; Qian, Lifang; Wu, Chenwei; Xu, Xinyue; Qu, Duoduo; Zhou, Lihua; Liu, Jia; Zhu, Qin; Wang, Chunhong; Zhao, Xiaolong (Frontiers in Endocrinology, 2024)
Objective: This study aims to examine the thyroid hormone profile and its association with severe coronavirus disease 2019 (COVID-19) in patients infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: This retrospective cohort study enrolled patients admitted to a tertiary hospital due to SARS-CoV-2 infection between February 18 and May 18, 2022. Clinical data were collected retrospectively from the electronic medical record system. Based on the thyroid function, patients were divided into five groups: normal, non-thyroid illness syndrome (NTIS), hypothyroidism, thyrotoxicosis, and unclassified. The association between thyroid function and severe COVID-19 was detected using multivariable logistic regression and restricted cubic splines analysis. Results: This study included 3,161 patients, with 7.7% of them developing severe COVID-19. 44.9% of the patients had normal thyroid function, 36.5% had NTIS, 6.7% had hypothyroidism, and 1.0% had thyrotoxicosis on admission. After adjusting for age, sex, and relevant clinical characteristics, NTIS and hypothyroidism were associated with increased risks of severe COVID-19 (odds ratio [OR] 2.38, 95% confidence interval [CI] 1.59-3.56 and OR 2.29, 95% CI 1.23-4.26, respectively), compared to normal thyroid function group. Among patients with NTIS or hypothyroidism, higher levels of total triiodothyronine (TT3) are associated with lower risks of severe COVID-19 (OR 0.73, 95% CI 0.64-0.82, for every 0.1nmol/L increase in TT3 level). Conclusion: Thyroid hormone profiles of NTIS or hypothyroidism are associated with increased risks of severe COVID-19. The decreased level of TT3 correlated with the increased risk of severe COVID-19 in patients with NTIS or hypothyroidism.